2002
DOI: 10.1126/science.1069531
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role of N-Terminal Arginylation in Cardiovascular Development

Abstract: Addendum to the main text (i) ATE1-/-embryos from ATE1 +/-intercrosses were present at the expected (~25%) frequency up to ~E13.5, but virtually no ATE1 -/-embryos were recovered alive by E17. Specifically, no ATE1 -/-mice were recovered amongst either 954 F 2 -generation pups of the C57BL/6J-129SvEv (mixed) background or 267 F 2 -generation pups of the 129SvEv (inbred) background. Timed intercrosses of ATE1 +/-mice were used to determine that ATE1 -/-embryos were present at approximately the expected (25%) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
371
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(388 citation statements)
references
References 22 publications
17
371
0
Order By: Relevance
“…Analysis of these phenotypes provides insights into the underlying molecular reasons for birth defects, and may allow us to predict major functional roles for proteins, whose functions have not been well established. An example of such a protein is arginyltransferase, Ate1, whose knockout in mice results in embryonic lethality with specific defects in heart development and angiogenesis that suggest that this gene and the corresponding posttranslational modification plays a critical role in cell migration in situ (Kwon et al, 2002). In agreement with that, Ate1 has been recently shown to regulate actin cytoskeleton, lamella formation, and lamellipodial protrusion (Karakozova et al, 2006), however the exact role of Ate1 in embryogenesis and cell motility remains to be uncovered.…”
Section: Migration-dependent Developmental Defects Key Cell Migrationmentioning
confidence: 88%
See 1 more Smart Citation
“…Analysis of these phenotypes provides insights into the underlying molecular reasons for birth defects, and may allow us to predict major functional roles for proteins, whose functions have not been well established. An example of such a protein is arginyltransferase, Ate1, whose knockout in mice results in embryonic lethality with specific defects in heart development and angiogenesis that suggest that this gene and the corresponding posttranslational modification plays a critical role in cell migration in situ (Kwon et al, 2002). In agreement with that, Ate1 has been recently shown to regulate actin cytoskeleton, lamella formation, and lamellipodial protrusion (Karakozova et al, 2006), however the exact role of Ate1 in embryogenesis and cell motility remains to be uncovered.…”
Section: Migration-dependent Developmental Defects Key Cell Migrationmentioning
confidence: 88%
“…(Carmeliet et al, 1999) L1-CAM Cell-cell adhesion Total Malformations of the nervous system, decreased nerve sensitivity, weak and uncoordinated hindlegs. (Dahme et al, 1997) Ate1 Arginyltransferase Total Embryonic lethality at E12-17 with defects in cardiovascular development and angiogenesis (Kwon et al, 2002) Calpain IV (Capn4) Protease Total Embryonic lethality at midgestation with defects in the cardiovascular system, (Arthur et al, 2000) Birth Defects Res C Embryo Today. Author manuscript; available in PMC 2009 June 1.…”
Section: Note On Nomenclaturementioning
confidence: 99%
“…The N-end rule relates the in vivo halflife of a protein to the identity of its N-terminal residue [9][10][11][12] ; the underlying proteolytic pathway is called the N-end rule pathway (Fig. 1).…”
mentioning
confidence: 99%
“…With N-terminal Asn and Gln, their conjugation to Arg is preceded by their enzymatic deamidation 14 . In metazoans, but not in fungi such as S. cerevisiae, N-terminal Cys is yet another tertiary destabilizing residue, in that the arginylation of Cys is preceded by its (apparently) enzymatic oxidation 12 (Fig. 1).…”
mentioning
confidence: 99%
“…This intuition turned out to be correct, and arginylation is now well accepted to be just as important as the phosphorylation [26,27]. The very first work, which clearly established the essential nature of ATE1 in mammals, is the experiment where the ATE1 gene was knocked out in mice, causing lethality due to heart defects in cardiovascular development and angiogenic remodeling during embryogenesis [28]. Their studies revealed that in the knockout mice, abnormal cardiac morphogenesis occurred.…”
mentioning
confidence: 99%